The Assesment Of Field Facilitator Performance and The Success Of Fish Farmers In Delima Jaya Village Kerinci Kanan District Siak Regency Riau Province - Sarnila '; Kusai '; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted on March 2016 in Delima Jaya Village, Kerinci Kanan District, Siak Regency, Riau Province. The objective of this research was to find out the assessment ofextentor, the success of fish farmer, to analyze the correlation between the extentor performance and the success of fish farmer. The method used in this research was survey method. The population of this research was the members of Kelapa Jaya Group who did fish cultivation which were 15 people. Therefore, the member of the respondents of this research was 15 people. Based on the result of research, the extentor performance in Delima Jaya village is categorized as good. It is proven by the final analysis scoring 279 which is around 226-316. Likewise the success of the fish farmers is also categorized as good, it is proven by the average scoring 681 which is around 501-750. The correlation is categorized as strong which proven by the Rank Spearman analysis scoring .658**. It means that ther is positive and significant (strong) correlation between the instructur’s performance and the success of the fish farmers which is around 0,600- 0,799. Keyword: Performance, Success